(untitled) (Inflexion Point Magazine, 2024)
Higher education functions must transcend the fundamental missions of research, extension, and teaching to promote the well-being of educational process stakeholders. This document presents the vision of senior managers of one public university in Bogotá, Colombia, about the elements that should be considered a university model of social responsibility. The project validated and applied an information collection instrument to 25 people, asking the participants to judge affirmation variables based on theoretical statements identified in the literature. A descriptive and quantitative analysis was performed through a statistical technique of factor analysis that identified central senior managers’ interests: physical-human environment, communication, sense of belonging, respect and collaboration treatment, environment and work climate; they also recommend taking actions to improve institution quality by disseminating and applying ethical principles and values in the fulfillment of its processes and functions and following up on responsible practices throughout time.